Между „памятью прошлого” и „памятью будущего”: проблема ретроспективной предвзятости и идентичности в Войне и мире Льва Толстого - Szubin, Roman (Studia Rossica Posnaniensia, 2026)
This article attempts to trace Leo Tolstoy’s critical approach to the Patriotic War of 1812 against the backdrop of Russia’s defeat in the Crimean War (1853–1855). In reconstructing the events of 1812, Tolstoy exposes a common flaw in Russian historiography and documents: retrospective bias. Following Tolstoy, the method of total distrust of historical sources and memoirs allow us to identify such forms of retrospective bias as anachronisms, argumentum ad consequentiam, backdating, and irresponsible thinking. Deconstructing the main myths of Russian history, Tolstoy consistently deposes the heroes of the war of 1812, as well as the internal party and covert warfare within the Russian army. Drafts for volume 3 of War and peace show that Tolstoy initially leaned toward the German version of the assessment of the key event – the Battle of Borodino. However, in the final version, the Russian historiographers’ version prevailed: Kutuzov’s moral victory over Barclay de Tolly, linked to the myth of a stolen victory. Considerable space is devoted to the analysis of one scene, which shows how, according to Tolstoy, the myth of the Russian victory in the Battle of Moscow was formed.